Pemeriksaan Kesehatan dan Edukasi Pencegahan Penyakit Ginjal Kronik pada Lansia di Nagari Sungai Buluh Selatan - Fitri Mailani; Rahmi Muthia; Emil Huriani; Sovia Susianty; Reni Prima Gusty; Elvi Oktarina; Muthmainah Muthmainah; Esthika Ariany Maisa; Arif Rohman Mansur (Warta Pengabdian Andalas, 2022)
Chronic kidney disease is one of the diseases that increase the risk in the elderly. Conducting health checks and education to maintain kidney health is an effort to improve the alertness of the elderly. This activity aims to serve the community by working on health checks and education on preserving kidney health for the elderly in the Nagari Sungai Buluh Selatan village. The method in this activity was to do a physical examination and blood check to see blood pressure, current blood sugar, and uric acid levels and continue by providing education related to maintaining kidney health in the elderly. This activity showed that 18 (33.9%) had grade 1 hypertension, and 30 (60.4%) elderly had high uric acid values. It is hoped that health checks and education activities are carried out regularly to increase awareness of the elderly to avoid other chronic diseases and improve their quality of life.